2021
DOI: 10.1101/2021.06.01.446609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prepubertal ovariectomy alters dorsomedial striatum indirect pathway neuron excitability and explore/exploit balance in female mice

Abstract: Decision-making circuits are modulated across life stages (e.g. juvenile, adolescent, or adult)—as well as on the shorter timescale of reproductive cycles in females—to meet changing environmental and physiological demands. Ovarian hormonal modulation of relevant neural circuits is a potential mechanism by which behavioral flexibility is regulated in females. Here we examined the influence of prepubertal ovariectomy (pOVX) versus sham surgery on performance in an odor-based multiple choice reversal task. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…A study by Wang et al found that estradiol treatment to OVX rats increased perseverative responding in an operant task and promoted a less efficient strategy in pursuit of food reward (Wang et al, 2008). Relatedly, we observed that prepubertal OVX females were less perseverative compared to sham females in an odor-based reversal task that was rewarded by food (Delevich et al, 2021). ERα signaling may negatively regulate cost sensitivity – i.e.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A study by Wang et al found that estradiol treatment to OVX rats increased perseverative responding in an operant task and promoted a less efficient strategy in pursuit of food reward (Wang et al, 2008). Relatedly, we observed that prepubertal OVX females were less perseverative compared to sham females in an odor-based reversal task that was rewarded by food (Delevich et al, 2021). ERα signaling may negatively regulate cost sensitivity – i.e.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to changes in growth and metabolism, peripuberty may be a sensitive period for the organization of adult behaviors across multiple domains including social, cognitive, and affective (Delevich and Wilbrecht, 2020; Larsen and Luna, 2018; Piekarski et al, 2017b; Schulz and Sisk, 2016). In particular, there is a growing interest in the influence of puberty and gonadal sex steroids on cognitive and decision-making processes (Delevich et al, 2021; Laube et al, 2017; Master et al, 2020; Orsini et al, 2022; Piekarski et al, 2017a). As food is a common primary reinforcer, it is important to understand how gonadal sex steroids influence motivation or willingness to work for food within contexts relevant to operant decision-making tasks.…”
Section: Introductionmentioning
confidence: 99%
“…129 Sex differences and estradiol sensitivity between MSN subtypes remains an active avenue of research. 127,130 These data predict that D2 subtype MSNs exhibit enhanced sensitivity to estradiol action upon mEPSC amplitude. Further testing with D1 or D2 labeled neurons in a relevant animal model must be conducted to confirm this prediction.…”
Section: Estradiol Rapidly Modulates Excitatory Synapse Properties In...mentioning
confidence: 85%
“…Rheobase is a strong predictor of whether a MSN is a D1 or D2 MSN subtype (D1 > D2; as reviewed previously 127,128 ), however, these strict definitions of MSN subtypes tend to break down in the nucleus accumbens core 129 . Sex differences and estradiol sensitivity between MSN subtypes remains an active avenue of research 127,130 . These data predict that D2 subtype MSNs exhibit enhanced sensitivity to estradiol action upon mEPSC amplitude.…”
Section: Estradiol Rapidly Modulates Excitatory Synapse Properties In...mentioning
confidence: 88%
“…Compatible with this idea, the ACC is thought to be important for regulating exploratory behavior 68,[73][74][75] . Furthermore, sex differences in exploration have been reported in a reinforcement learning task 7 and exploratory choices in a reversal learning task have been linked to the effect of sex hormones on D2R MSNs in the DMS in females 76 .…”
Section: Previous Behavioral Evidence For Sex Differences In Value-ba...mentioning
confidence: 99%